Ultrasound pretreated hot air drying of spine gourd (Momordica dioica Roxb. Ex Willd): The effect on quality attributes - Yogesh Kumar; Ankan Kheto; Lochan Singh; Vijay Singh Sharanagat (Food Chemistry Advances, 2023)
Spine gourd (SG) is a nutritionally and medicinally rich seasonal vegetable grown in tropical areas. Therefore, the present study accessed the effect of drying temperature (40, 50, 60, and 70 °C) on chlorophyll, ascorbic acid, proximate, antioxidant, and minerals contents of ultrasound (US) pretreated SG. The increase in drying temperature (40−70 °C) after pretreatment increased the total flavonoids, fiber, protein and ash content compared to freeze-dried (control) sample. In contrast, elevated drying temperature significantly degraded the chlorophyll, ascorbic acid, carbohydrates, fat, total phenolic, and DPPH activity. In addition, the effect of drying temperature on the mineral contents was comparable and a significant variation was observed between control and US pretreated samples. The FTIR spectra revealed that functional group integrity was preserved even at higher drying temperatures. Conclusively, the US pretreated sample dried at 40 °C showed a better nutritional content (comparable to freeze-dried samples) than those dried at higher temperatures. However, samples dried at 70 °C were rich in protein and antioxidants.